Strategi Pemasaran Usaha Makro Kecil Menengah (UMKM) Terhadap Penjualan Lemang Tapai Di Bengkulu - Dahnia, Cica Tri; Febliansa, M. Rahman; Sachanovarissa, Silke; Hardinata, Dodi (Jurnal Dehasen Untuk Negeri, 2025)
In Micro, Small, and Medium Enterprises (MSMEs) is a business sector that includes small and medium-scale business units. The benefits of the existence of MSMEs can encourage local economic growth and economic equality. The problem in this lemang tapai research is the decline in customers or income and also not following the era where this business is still sold in places or stalls have not been sold through digital media or social media. This study aims to provide an explanation of marketing through digital or online media, where with this social media people can find out about the sale of lemang tapai and also the sale of lemang tapai can develop even wider